2019
DOI: 10.1111/cmi.13092
|View full text |Cite
|
Sign up to set email alerts
|

A sphingolipid synthesis‐related protein OrmA in Aspergillus fumigatus is responsible for azole susceptibility and virulence

Abstract: Previous studies identified that the budding yeast Saccharomyces cerevisiae have two sphingolipid synthesis‐related proteins, Orm1p and Orm2p, that negatively regulate the activities of SPT, which is a key rate‐limiting enzyme in sphingolipid synthesis. However, little is known about whether sphingolipids in the cell membrane, which are closely related to ergosterols, could affect the efficacy of azole drugs, which target to the ergosterol biosynthesis. In this study, through genome‐wide homologue search analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
(73 reference statements)
1
26
0
Order By: Relevance
“…Although Orm proteins are, overall, highly conserved in animals, plants, and fungi, the Orm proteins in fungi have specific characteristics. Notably, there are seven conserved amino acid residues-RRRRSSS-near the N-terminal region of fungal Orm proteins (Zhai et al, 2019); the three serine residues can be phosphorylated, leading to inactivation of OrmA. These data indicate that these specific sites of OrmA may serve as targets for developing novel antifungal therapies, and, hence, inhibitors that act on these specific sites might improve the efficacy of azole drugs without any toxicity to host cells.…”
Section: P Otential For S Phing Olipid B I Osynthe S Is a S A Novelmentioning
confidence: 99%
See 4 more Smart Citations
“…Although Orm proteins are, overall, highly conserved in animals, plants, and fungi, the Orm proteins in fungi have specific characteristics. Notably, there are seven conserved amino acid residues-RRRRSSS-near the N-terminal region of fungal Orm proteins (Zhai et al, 2019); the three serine residues can be phosphorylated, leading to inactivation of OrmA. These data indicate that these specific sites of OrmA may serve as targets for developing novel antifungal therapies, and, hence, inhibitors that act on these specific sites might improve the efficacy of azole drugs without any toxicity to host cells.…”
Section: P Otential For S Phing Olipid B I Osynthe S Is a S A Novelmentioning
confidence: 99%
“…Many studies highlight that sphingolipids are signaling molecules that play an important role in several cellular processes (Chen et al ., 2013; Montefusco et al ., 2013; Huang et al ., 2014; Rego et al ., 2014; Teixeira et al ., 2016; Villasmil et al ., 2016; Mohammad et al ., 2018; Liu et al ., 2019). Interestingly, recent studies have confirmed that sphingolipids could contribute to azole resistance (Gao et al ., 2018; Garnaud et al ., 2018; Zhai et al ., 2019). Therefore, in this section, we will focus on the role of sphingolipids as signaling molecules in azole drug resistance.…”
Section: Role Of Fungal Sphingolipid Synthesis In Azole Resistancementioning
confidence: 99%
See 3 more Smart Citations